Manipulation of resource allocation to increase fecundity in Mimulus gemmiparus - Chu, Kevin, author; Steingraeber, David, advisor; Funk, Chris, committee member; Hufbauer, Ruth, committee member (Colorado State University. Libraries, 2016)
Mimulus gemmiparus W. A. Weber, a Colorado endemic, is a rare species that is at risk of becoming endangered. Reproduction in M. gemmiparus is solely by vegetative propagules (bulbils), which function analogously to seeds; sexual reproduction has not been observed in the wild. Manipulation of resource allocation in this plant may shift resources allocated for sexual reproduction to vegetative growth; the investment in increased vegetative growth should result in a direct increase in fecundity. Two experiments were conducted to examine the effects of redistribution of resources and change in meristem fate. The first experiment used plants grown in greenhouse conditions; seemingly nonfunctional floral buds or floral buds and shoot apical meristems were removed to potentially increase bulbil production. The second experiment used plants grown indoors under growing lamps to produce plants that were similar in size to those found in their natural habitats; their shoot apical meristems were removed to potentially induce branching and thus increase vegetative growth to increase bulbil production. Removal of floral buds or removal of both floral buds and shoot apical meristems in a greenhouse environment doubled the number of bulbils produced per plant, increased by approximately two-thirds the total bulbil biomass per plant, increased the ratio of bulbil count to stem biomass, and increased the ratio of bulbil biomass to stem biomass; however, there was a trade-off between having greater number of bulbils and individual bulbil biomass. Solely removing the shoot apical meristem in a low-light environment had no effect on bulbil production; although branching was induced, the primary branches remained small and did not elongate. Secondary branches were formed only on plants that had their shoot apical meristem removed. The total numbers of shoot axes per plant were not significantly different between the control and treatment group; the induction of branching seemingly produces a compensatory effect, but not overcompensation for the removal of the shoot apical meristem. In both experiments, stem biomass did not differ between the control and treatment group(s). Lighting condition in the environment the plants grew in had the greatest effect on stem development, and manipulation of meristems to form new shoots did not increase plant size. Bulbil yield may be increased in greenhouse conditions by manipulation of allocation from sexual reproduction to vegetative growth.
Keywords: fecundity; resource allocation; Mimulus gemmiparus; Bulbil